HYDROLIZE CANE WASTE To GLUCOSE by Trichoderma viride (Study on Cane Waste Concentration and Fermentation Time) - Saparianti, Ella; Dewanti, T.; Dhoni, S. K. (Fakultas Teknologi Pertanian Universitas Brawijaya, 2004)
Trichoderma viride is the one of selulolitic microorganisms that can produce glucose from selulose rich material such as cane waste. This research was conducted to study the effect of cane waste concentration and fermentation time on glucose yield of the liquid. Completely Randomized Block Design (CRBD) was employed on this research with two factors. Factor I is cane waste concentration (2, 5, 8%) and factor two is fermentation time (5, 10 15 days). The result showed that cane waste concentration significantly (α=0,01) affected glucose yield, selulolitic activity, viscosity, and total dissolved solid. Fermentation time siginificantly (α=0,01) affected glucose yield, total molds, selulolitic activity, viscosity, and total dissolved solid. The high glucose yield (13,442%) was reached at cane waste concentration of 8% and fermentation time of 15 days. This treatment caused selulose of 18,829% was hydrolyzed with selulolitic activity of 74,678 NCU, total molds of 65,33 x 105, viscosity of 9,387 x 10-3 centipoise , and total dissolved solid of 6,47 (brix). Key words : cane waste, glucose, selulolitic activity, Trichoderma viride